LA TEORÍA DE LA ACCIÓN SOCIAL DE J. HABERMAS - Prior Olmos, Ángel (Daimon Revista Internacional de Filosofia, 1991)
The article distinguishes three essential aspects in Habermas´s Theory of Social Action. Firstly, it studies the conformation of Habermas´s thought from his early distinctions between "work" and "interaction" to last formulations of "teological/estrategic action" and "communicative action". It points out the problematic character of the first distinction, in which there is interest in connecting with the contributions of Hegel and Marx about the role of the work in social life. Secondly, it analyses the typology of action in his 'Theory of Communicative Action', emphasising the problematic character of central concept of "communicative action". It debates the question of its nature: an analytical or real distinction, and it points out Habermas´s attempts to resolve some objections. Finaly, Theory of Social Action is a metatheoric proposal as wll as a central element of the Theory of Social Evolution, which Habermas wants to oppose to Horkheimer´s and Adorno´s theories. The article hishlights the role of communicative action in the reproduction of symbolic structures of 'Lebenswelt', but at the end, in the evolution of social formations, Habermas recovers the classical Marxist thesis about the relation between productive forces and relations of production.